Information, Education, and Communication (IEC) Intervention: A strategic approach to improve knowledge, attitude and behavioural changes regarding organ and tissue donation among health science students of Maharashtra - Tambe, Rahul; B. Bangal, Vidyadhar (Journal of Neonatal Surgery, 2025)
Introduction: Organ and tissue donation is a life-saving act that plays a vital role in modern healthcare. Yet, there is a significant gap in awareness, knowledge, and positive attitude among the general population, especially youth. As future healthcare providers, health sciences students are expected to have accurate knowledge and a favourable attitude towards organ and tissue donation. In the current scenario, with increasing demand for organ transplants and low donation rates in India, there is an urgent need to promote awareness and behavioral change. Information, Education, and Communication (IEC) activities serve as an effective strategy to educate and motivate young health professionals about organ and tissue donation. Strengthening their knowledge and attitude can help in building a supportive environment for organ donation practices in the future. Methodology: The present study adopted a quantitative research approach with a quasi-experimental design consisting of experimental and control groups. The study was conducted among 600 first-year Health Sciences students selected through purposive sampling technique from various medical, nursing, and BAMS colleges of health science of Maharashtra. The data were collected using structured tools such as a knowledge questionnaire, behavioural change scale, and attitude scale. The IEC (Information, Education, and Communication) activity was implemented for the experimental group using educational sessions, posters, pamphlets, and audiovisual aids to enhance awareness regarding organ and tissue donation. Pre-test and post-test assessments were done to evaluate the effectiveness of the intervention. Ethical permission was obtained from the institutional authorities, and informed consent was taken from participants. Results: The present study adopted a quantitative research approach with a quasi-experimental research design incorporating experimental and control groups to assess the effectiveness of significant association was found between the pre-test knowledge score and religion (p=0.044*), whereas other socio-demographic variables showed no significant association (p>0.05) with the pre-test knowledge score among health sciences students in the experimental group. Discussion: The study revealed that IEC activities were effective in enhancing knowledge, improving attitude, and strengthening behavioural intentions regarding organ and tissue donation among health sciences students. The educational intervention positively influenced students irrespective of their socio-demographic background. However, religion was found to have a significant association with pre-test knowledge. Integrating organ donation awareness programs in health sciences education is essential for promoting positive behaviour and future advocacy